2011
DOI: 10.1149/1.3585668
|View full text |Cite
|
Sign up to set email alerts
|

Annealing Effect on Photovoltaic Performance of Hybrid P3HT/In-Situ Grown CdS Nanocrystal Solar Cells

Abstract: The CdS nanocrystals with different aspect ratios (ARs) can be synthesized directly in the presence of conjugated polymer poly(3-hexylthiophene-2,5-diyl) (P3HT). The UV-vis spectra of the composite films show a blue shift of the p-p * transition band with an increasing aspect ratio (AR) of the CdS nanocrystals, which was attributed to the destruction of the ordered structure of polymer chains as supported by PL measurements. Atomic force microscope measurements on P3HT/CdS film also demonstrate the aggre-gatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 34 publications
2
8
0
Order By: Relevance
“…Conjugation system in P3HT causes two peaks at 522 and 556 nm and a shoulder at 605 nm to appear in the UV-Vis graph. A similar result has been obtained by the Liao research group [31]. The peaks attribute to π-π* transition or the order of intermolecular chains of the polymer, while the shoulder is due to crystallization of polymer [32,33].…”
Section: Resultssupporting
confidence: 85%
“…Conjugation system in P3HT causes two peaks at 522 and 556 nm and a shoulder at 605 nm to appear in the UV-Vis graph. A similar result has been obtained by the Liao research group [31]. The peaks attribute to π-π* transition or the order of intermolecular chains of the polymer, while the shoulder is due to crystallization of polymer [32,33].…”
Section: Resultssupporting
confidence: 85%
“…Hybrid P3HT/CdS layers containing nanorods with higher aspect ratio exhibit more efficient photoluminescence quenching as well as higher solar cell efficiencies compared to devices using spherical nanoparticles [95]. This can be attributed to an increased interaction strength of the nanostructures to the sulfur atoms in P3HT with increasing aspect ratio, as analysed by 1 H-NMR spectroscopy [96]. Solar cells prepared with nanorods having an aspect ratio of 16 showed the best PCEs exhibiting values up to 2.95%, which are currently the highest reported values for hybrid solar cells prepared via in situ routes [96].…”
Section: Figure 6 A: Dark Field Scanning Tem Image Of Pbs Nanocrystamentioning
confidence: 98%
“…The positive effect of the in situ prepared nanorods concerning photovoltaic applications was elaborated in detail by Liao et al [95,96]. Hybrid P3HT/CdS layers containing nanorods with higher aspect ratio exhibit more efficient photoluminescence quenching as well as higher solar cell efficiencies compared to devices using spherical nanoparticles [95].…”
Section: Figure 6 A: Dark Field Scanning Tem Image Of Pbs Nanocrystamentioning
confidence: 99%
See 1 more Smart Citation
“…The T g of P3HT has been reported to be -14, 12, and 110 o C by different research groups [19][20][21][22], and T m of P3HT was observed around 200-230 o C [22,23]. Since T g is affected by molecular weights and structural regioregularity of polymers, the measurement of T g of a certain P3HT can be varied with different material sources and characterization techniques.…”
Section: Accepted Manuscriptmentioning
confidence: 99%